Komunikasi Antarbudaya Etnis Tionghoa Dan Pribumi Di Pasar Cinde Palembang - Eni Murdiati; Hanifa Hanifa; Muzaiyanah Muzaiyanah (CV. ITTC INDONESIA, 2023)
This study discusses the process of intercultural communication between the Chinese and indigenous ethnic groups, and the factors that influence the process of intercultural communication between the Chinese and indigenous ethnic groups at Pasar Cinde Palembang. This study used a descriptive qualitative research method, in which the data collection was carried out by observation, interviews and documentation obtained from informants. by using the theory of intercultural communication which emphasizes that intercultural communication occurs when the communicator and communicant come from different cultures and social interactions. The results of this study indicate that: 1. the process of intercultural communication between ethnic Chinese and natives at Pasar Cinde Palembang is running effectively. In its implementation found the existence of primary and secondary communication. The form of communication is interpersonal communication that occurs every day, both between traders and traders with buyers. 2. Factors that influence the process of intercultural communication between Chinese and indigenous ethnicities are supporting factors such as language acquisition, means of communication, thinking skills, and mutual respect, and there are inhibiting factors, namely stereotypes, prejudice, and language which can be handled well by the Chinese ethnicity and native.